O entrelugar da experimentação no romance latinoamericano contemporâneo: Manuel Puig e Caio Fernando Abreu - Wanderlan da Silva Alves (Estudos de Literatura Brasileira Contemporânea)
We analyze the speech and forms of narrative experimentation developed by Manuel Puig and Caio Fernando Abreu in Boquitas pintadas and Onde andará Dulce Veiga? from the notion of interplace. Such a place, unstable and marked by symbolic exchanges, allows us to think, in both novels, about the conditions under which subjective experiences and aesthetic are triggered. By presenting themselves as possible in the context in which such works are produced, marked by the excess of information, the publishing of market demands, the cultural industry determinations, and by the dialogue with mass culture and a massive and diversified public. Whenever it is possible, such considerations extend even to determined experimentalist literary production, developed in Latin America, between the 70s and 90s approximately.